New analytical procedure based on a cellulose bag and ionic exchanger with p-aminobenzoic acid groups for differentiation of labile and inert metal species in aquatic systems - Rosa, Andre Henrique; Goveia, Danielle; Bellin, Iramaia C.; Lessa, Suzan da Silva; Dias Filho, Newton L.; Padilha, Pedro de Magalhaes (Springer, 2006)
A new procedure was developed for the in situ characterization of the lability of metal species in aquatic systems by using a system equipped with a diffusion membrane and cellulose organomodified with p-aminobenzoic acid groups (DM-Cell-PAB). To this end, the DM-Cell-PAB system was prepared by adding cellulose organomodified with p-aminobenzoic acid groups (Cell-PAB) to pre-purified cellulose bags. After the DM-Cell-PAB system was sealed, it was examined in the laboratory to evaluate the influence of complexation time, mass of exchanger, pH, metal ions (Cu, Cd, Fe, Mn, and Ni), and concentration of organic matter on the relative lability of metal species. It was found that the pH and kinetics strongly influence the process of metal complexation by the DM-Cell-PAB system. At all pH levels, Cd, Mn, and Ni showed lower complexation with Cell-PAB resin than Cu and Fe metals. Note that relative lability of metals complexed to aquatic humic substances (AHS) in the presence of Cell-PAB resin showed the following order: Cu congruent to Fe >> Ni > Mn=Cd. The results presented here also indicate that increasing the AHS concentration decreases the lability of metal species by shifting the equilibrium to AHS-metal complexes. Our results indicate that the system under study offers an interesting alternative that can be applied to in situ experiments for differentiation of labile and inert metal species in aquatic systems.
Keywords: aquatic humic substances; metal species; lability; cellulose modified with p-aminobenzoic acid groups